2023
DOI: 10.1101/2023.01.18.524646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex chromosome evolution in beetles

Abstract: Beetles are the most species-rich group of animals and harbor diverse karyotypes. Most species have XY sex chromosomes, but X0 sex determination mechanisms are also common in some groups. We generated a whole-chromosome assembly of a beetle species with a neo-sex chromosome and utilize eleven additional beetle genomes, to reconstruct karyotype evolution across Coleoptera. We identify ancestral linkage groups, termed Stevens elements, that share a conserved set of genes across beetles. While the ancestral X chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
(86 reference statements)
3
8
0
Order By: Relevance
“…While it is tempting to speculate that the sex-linkage of (a part of) chromosome 2 may be advantageous, it is also possible the region of the genome corresponding to I. elegans chromosome 2 was incorporated into the X chromosome of insects and subsequently lost in C. septempunctata, A. pisum, and S. americana. Finally, rearrangements such as fissions and fusions are common in Coleoptera (Bracewell et al 2023) and Hemiptera (Mathers et al 2021), and the above result may simply occur because of the taxa chosen within these orders. More extensive sampling would be needed to distinguish between these three hypotheses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is tempting to speculate that the sex-linkage of (a part of) chromosome 2 may be advantageous, it is also possible the region of the genome corresponding to I. elegans chromosome 2 was incorporated into the X chromosome of insects and subsequently lost in C. septempunctata, A. pisum, and S. americana. Finally, rearrangements such as fissions and fusions are common in Coleoptera (Bracewell et al 2023) and Hemiptera (Mathers et al 2021), and the above result may simply occur because of the taxa chosen within these orders. More extensive sampling would be needed to distinguish between these three hypotheses.…”
Section: Resultsmentioning
confidence: 99%
“…However, the systematic sequencing of species of various insect orders has shifted this view. First, studies that compared multiple species within orders have detected conservation of the X-linked gene content in Hemiptera (Pal and Vicoso 2015;Mathers et al 2021), Orthoptera (Xinghua et al 2022), and Coleoptera (Bracewell et al 2023), despite the diversity of sex determination systems found in these groups (including X0, XY, multiple X chromosomes, but also PGE and haplodiploidy (Blackmon et al 2017)). The only currently known exception to the conservation of an X chromosome within an insect order is Diptera, where sex-chromosome turnover from the ancestral element F has been documented extensively involving many different chromosomal elements of the genome (Vicoso and Bachtrog 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of sex chromosomes in Coleoptera is a recurring topic in the literature. Most species present a Xy sex chromosome system [ 52 ] and share an ancestral X chromosome [ 53 ] but with several morphological patterns. Furthermore, the derivations of this basal system may have resulted from fusion, fission, and other chromosome rearrangements within this order, showing a high potential for Y loss and gain [ 9 , 10 , 52 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identi ed autosomal contributions (or losses) to the X chromosome, which involved three different autosomes (Figures S4-S6). Within Coleoptera, synteny across the X chromosome has been reported to be highly conserved, with conserved blocks going back to 350 MY [21]. The age of the X chromosome, could go further back to 450 MY, as X chromosome syntenic blocks have been found across nine insect orders, including true bugs, dragon ies, and grasshoppers [67].…”
Section: Luciola Italica and Lamprohiza Splendidula Genomesmentioning
confidence: 99%
“…Overall, expression imbalance between the autosomes and between the sexes, is hypothesized to be highly detrimental, so much, that highly complex mechanisms have evolved to restore dosage balance in some taxa independently [19,20]. Some beetles show full X DC [21], but how conserved is DC within beetles and what is its status in re ies still needs to be explored.…”
Section: Introductionmentioning
confidence: 99%